2009
DOI: 10.1111/j.1600-0854.2008.00861.x
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle Motion and Fusion are Altered in Chromaffin Cells with Increased SNARE Cluster Dynamics

Abstract: The expression of SNAP-25 fused to green fluorescent protein (GFP) has been instrumental in demonstrating SNARE role in exocytosis. The wild-type GFP-SNAP-25 and a D9 form, product of botulinum neurotoxin A activity, the main ingredient in the BOTOX preparation, were employed here to study SNARE implication in vesicle mobility and fusion in cultured bovine chromaffin cells, a neuroendocrine exocytotic model. Using total internal reflection fluorescent microscopy, we have identified membrane microdomains of 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…Vesicles were visualized using GFP-synaptobrevin-II, as described previously (Gil et al, 2002). In other experiments, vesicles were stained with 2 M Acridine Orange, and the granule position was assessed by the red Acridine Orange fluorescence of mature acidic vesicles; their fusion was followed by detection of the green flashes produced after matrix neutralization during exocytosis (Lopez et al, 2009). To combine cytoskeletal images with TIRFM, the light from the halogen lamp used for light transmission was filtered to give red light (LP590 filter) for the simultaneous visualization of the labelled vesicles.…”
Section: Total Internal Reflection Fluorescence Microscopy Studies Ofmentioning
confidence: 99%
“…Vesicles were visualized using GFP-synaptobrevin-II, as described previously (Gil et al, 2002). In other experiments, vesicles were stained with 2 M Acridine Orange, and the granule position was assessed by the red Acridine Orange fluorescence of mature acidic vesicles; their fusion was followed by detection of the green flashes produced after matrix neutralization during exocytosis (Lopez et al, 2009). To combine cytoskeletal images with TIRFM, the light from the halogen lamp used for light transmission was filtered to give red light (LP590 filter) for the simultaneous visualization of the labelled vesicles.…”
Section: Total Internal Reflection Fluorescence Microscopy Studies Ofmentioning
confidence: 99%
“…A previous nanoscopy study based on stimulated emission depletion (16), as well as other studies (17)(18)(19), have investigated the distribution of syntaxin and other synaptic proteins on the membrane and have indicated syntaxin partitioning into nano-sized clusters (16, 17, 19 -23). Sieber et al (16) suggested the existence of two pools of syntaxin: clustered and as single freely diffusing molecules.…”
mentioning
confidence: 99%
“…Therefore, it is suggested that even at the time of experiencing exocytosis, granules interact with cytoskeletal elements. In order to prove such interaction we studied the precise localization of exocytosis in relation to cytoskeletal structures by in vivo observation of the exocytotic events using TIRFM observation of acridin orange (AO) loaded granules (López et al, 2009) and the cytoskeletal structures using transmitted light. As can be seen in the example of Fig.…”
Section: Fusions Occur In the Border Of Cytoskeletal Cagesmentioning
confidence: 99%
“…Expression of DsRed and GFP-SNAP-25 was performed as described recently (López et al, 2009). The cDNA corresponding to the SNAP-25a isoform (Bark and Wilson, 1994) was cloned into the XhoI and BamHI sites of pDsRed-C3 or pEGFP-C3 (Clontech, Palo Alto, California) to express this protein fused in-frame at the C-terminus.…”
Section: Expression Of Dsred and Gfp-snap-25 Constructs In Chromaffinmentioning
confidence: 99%
See 1 more Smart Citation